Lymphatic filariasis in Nilphamari district: An endemic area in Bangladesh (Bangladesh Journal of Zoology, 2018)
The present study was carried out in Nilphamari district, Filaria Hospital of Nilphamari district and from randomly selected three villages of Nilphamari Sadar and Paurasava, Sayedpur, Domar, Dimla, Joldhaka and Kishoreganj. The objectives of this study were to find out the status of lymphatic filariasis (LF) in Nilphamari district: An endemic area for LF in Bangladesh. The investigation was carried out among the inhabitants of the villages and the outdoor patients of Filaria Hospital in Nilphamari through a formatted questionnaire. The current status of this disease was 4.43% in Nilphamari Sadar and 3.25% in Paurasava, 4.10% in Sayedpur and similarly 4.82% in Domar, 5.86% in Dimla, 3.85% in Joldhaka and 4.70% in Kishoreganj. In Nilphamari district, it was found that male were more susceptible (58.84%) than female (41.16%). 76.22% male patients had hydrocoele and the disease showed its highest prevalence (41.16%) in the age group of 41-60 years.Bangladesh J. Zool. 46(1): 11-19, 2018